VD_FINDINFO HC / 2020 / 679 vom 2. Oktober 2020 - VD Tribunal cantonal (2020)
PROTECTION DE L'UNION CONJUGALE, REVENU HYPOTHÉTIQUE, REJET DE LA DEMANDE, OBLIGATION D'ENTRETIEN | 125 al. 3 CC, 176 CC, 277 al. 2 CC, 317 al. 1 CPC (CH)